The acceptance of Bank Rakyat services through their corporate social responsibilities (CSR) provided by Bank Rakyat Jasin Melaka / Robieahton Kamarudin - Kamarudin, Robieahton (Faculty of Business and Management, 2008)
The purpose of this research was to enhance our understanding on several selected dimensions that influence the acceptance of services through the corporate social responsibilities provided by Bank Rakyat Jasin. The model investigated three major variables that may influence the acceptance of Bank Rakyat services which were CSR activities, product and services, and employee's skill and behavior. The results show that these three variables are able to explain the acceptance of Bank Rakyat services. The findings showed that most of the customers were accept the services through the CSR activities in achieving social or environmental outcomes when there is a direct link to profit which we can the increasing of the profits and also the increasing numbers of the account holder for 3 years. This approach to CSR requires that the resources applied to CSR activities must have at least as good a return as that these resources could generate if applied anywhere else. This analysis drastically narrows the possible scope of CSR activities. In this study, we used interviews and questionnaire techniques for data collection. Based on frequency table including means, mode and standard deviations, a clear findings and result is observed.